Inner-shell autoionization resonances along Mg isoelectronic sequence. (August 2015) - Sindhu, K; Varma, H R; Deshmukh, P C; Manson, S T
Synopsis: Studies of the 2s → np autoionization resonances using a combination of Relativistic Random Phase Approximation (RRPA) and Relativistic Multichannel Quantum Defect Theory (RMQDT) of Mg isoelectronic sequence are reported.